Detection and identification of aquatic mycobacteria in formalin-fixed, paraffin-embedded fish tissues - Pourahmad, F (Journal of fish diseases, 2009)
The isolation of mycobacteria from field samples is problematic, and isolation of the bacterium is sometimes not even attempted. The detection of mycobacteria through traditional histology using formalin-fixed, paraffin-embedded (FFPE) tissues is neither sensitive nor specific. However, detection of mycobacterial DNA from FFPE specimens, suspected of being infected with mammalian mycobacteriosis, is a routine clinical procedure. In the present study, a polymerase chain reaction (PCR)-based method was used to detect and identify mycobacteria in FFPE specimens sampled from fish suspected of being infected with fish mycobacteriosis. A total of 45 fish tissue samples, comprising of 12 tissue samples obtained from experimentally infected fish and the remainder from fish naturally infected with mycobacteria, were analysed using a PCR protocol which amplifies a fragment of the mycobacterial 65 kDa heat-shock protein (hsp65) gene. PCR-restriction enzyme analysis and/or sequencing were employed to further analyse the PCR amplicons. The PCR results were compared with those obtained by histology and culture. Mycobacterial DNA was detected in 34 of the 45 samples examined, of which 16 samples (47%) showed granulomatous reactions on histological examination. Using histology as the gold standard, no false-negative PCR results were obtained. Also, considering the presence or absence of granulomas as a diagnostic criterion, the sensitivity and specificity of PCR in 42 of the FFPE tissues were 16/16 (100%) and 8/26 (approximately 30.8%), respectively. Corresponding microbiological cultures were available for 15 cases, of which 13 were pure Mycobacterium cultures. Of these, 13 were PCR positive (100% sensitivity and 50% specificity). The PCR-based methods used here proved sensitive, specific and rapid for the detection of mycobacteria in routinely processed paraffin wax-embedded and formalin-fixed histological samples, and the results of the study suggest that this method has potential use in retrospective epidemiological studies